Implementasi Cost of Quality Pekerjaan Bekisting Konvensional dan Semi Sistem Studi Kasus Proyek Embung KIPP Lanjutan dan DAS Pemaluan - Mukhamad Subkhi; Ervina Ahyudanari (Jurnal Impresi Indonesia, 2025)
Indonesia's construction industry faces challenges in maintaining quality while optimizing costs, especially in the selection of formwork methods that greatly affect the quality of concrete structures and overall project efficiency. This study aims to analyze the implementation of Cost of Quality (COQ) in conventional and semi-system formwork for the KIPP Continuation Dam and DAS Pemaluan project. The research method uses a comparative quantitative approach with COQ analysis covering prevention, appraisal, internal failure, and external failure costs. Results show that conventional formwork COQ is 87.14%, dominated by internal failures (43.54%) due to vulnerability to installation errors and material damage. Meanwhile, semi-system formwork COQ is 21.77% with a more balanced distribution between prevention costs (44.04%) and internal failures (15.62%). Technical planning shows conventional formwork requires support spacing of 170mm, horizontal supports 810mm, and braces 690mm, while semi-system requires 250mm, 900mm, and 1065mm respectively. Although conventional formwork material costs are 63% cheaper than semi-system, the high total quality costs make semi-system more efficient overall with more consistent performance and minimal rework risks.